2018
DOI: 10.1016/j.commatsci.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study of intercalation complexes of kaolinite with simple amides as primary intercalation reagents

Abstract: Delamination/exfoliation of book-like kaolinite particles is one of the most promising ways to produce aluminosilicate nanoscrolls. For the delamination of the kaolinite layers, multi-step intercalation/deintercalation procedures are used. In the first, direct intercalation step, the intercalation reagents are typically small organic molecules possessing high dipole moment. We modeled, evaluated and compared the incorporation features of formamide, urea and Nmethylformamide molecules into the interlayer space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 51 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…Parameters and topologies within the simulations were extracted from the INTERFACE force field . The INTERFACE force field can operate as an extension of several commonly used harmonic force fields, including CHARMM, thus enabling simulations of toxin binding on organic/biomolecular and inorganic interfaces, including montmorillonite . The topologies of glyphosate and paraquat were generated through CGENFF with low penalties using the molecular structures of the two molecules at pH 2 and 7.…”
Section: Methodsmentioning
confidence: 99%
“…Parameters and topologies within the simulations were extracted from the INTERFACE force field . The INTERFACE force field can operate as an extension of several commonly used harmonic force fields, including CHARMM, thus enabling simulations of toxin binding on organic/biomolecular and inorganic interfaces, including montmorillonite . The topologies of glyphosate and paraquat were generated through CGENFF with low penalties using the molecular structures of the two molecules at pH 2 and 7.…”
Section: Methodsmentioning
confidence: 99%
“…Kaolinite layers can be simply regarded as uncharged reference clay layers. Nevertheless, kaolinite can be also delaminated under certain conditions (Kristóf et al, 2018). Although the spacing of the clay layers was allowed to change in the simulations, it practically did not, due to the fixed amount of the interlayer aqueous phase.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters for kaolinite and montmorillonite were taken from the INTERFACE (v1.5) force field, and the other parameters including those of the interlayer Na + ions of montmorillonite were from the CHARMM database. Based on previous works (Ható et al, 2014;Kristóf et al, 2018) we found INTERFACE a suitable force field for modelling kaolinite. The CHARMM27 force field variant implemented in GROMACS (Bjelkmar et al, 2010) was used for inorganic ions.…”
Section: Model Construction and Computational Detailsmentioning
confidence: 98%
“…2:1 layer silicates such as smectites are excellent candidates for the formation of HCMs; in fact, because of their high cation exchange capacity and swelling behavior, they can intercalate even through fast one-step reaction cations or polar molecules that give peculiar properties to the resulting structure. ,, On the other hand, the intercalation of cations and molecules in 1:1 layer silicates such as kaolinite, although it is possible, is more difficult as the interactions are usually limited to exposed edges and sheets (adsorption), leaving the layer structure almost unchanged. In fact, unlike in smectite, kaolinite layers are bound by reactive hydrogen bonds which could not be easily broken; consequently, even if the basal spacing of kaolinite can be extended to values higher than the original 0.71 nm, it is very difficult to induce swelling through a fast one-step reaction.…”
Section: Introductionmentioning
confidence: 99%